FROM FTA TO EXPORT EARNINGS: UNLOCKING INDONESIA’S EXPORT POTENTIAL TO CHILE THROUGH TRADE COMPLEMENTARITY, RCA, AND NTM MITIGATION - Rahayu Kusumawati; Muh. Nurkhamid (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to explain why trade intensity between Indonesia and Chile remains low despite the implementation of the Indonesia–Chile Comprehensive Economic Partnership Agreement (IC-CEPA), which has provided zero-tariff access for 6,704 tariff lines since August 2019. Using a descriptive quantitative approach and secondary data from UNCOMTRADE, WITS, and UNCTAD TRAINS for the period 2019–2024, this study examines four integrated indicators: the Trade Intensity Index (TII), Trade Complementarity Index (TCI), Revealed Comparative Advantage (RCA), and Export Market Penetration (EMP), complemented by an analysis of non-tariff measures (NTMs). The findings reveal that although Indonesian exports to Chile increased significantly to US337.5 million in 2024, generating a record trade surplus of US202 million, the TII remains low at 0.29 substantially below Peru’s TII of 0.61, despite Peru not having a free trade agreement with Indonesia. This paradox reflects a mismatch between strong structural potential and actual trade performance. While trade structures are highly complementary (TCI = 58.12) and Indonesia demonstrates strong competitiveness in key products such as cotton yarn (RCA = 77.40) and vegetable oils (RCA = 40.53), actual market penetration remains limited (EMP < 15%). This gap is primarily attributed to non-tariff barriers, particularly Sanitary and Phytosanitary (SPS) measures and Technical Barriers to Trade (TBT), as well as the possible underutilization of Certificates of Origin (COOs). The novelty of this study lies in its first-time integration of these four indicators within an IC-CEPA diagnostic framework, shifting the analytical focus from aggregate export growth to micro-level, product specific constraints. The findings provide an evidence-based foundation for policy recommendations aimed at enhancing FTA utilization and transforming preferential tariff access into sustainable export earnings.